Rosai-Dorfman disease of the breast: A case report - Ongchaiwattana, Amornthip; Jitpasutham, Tikamporn; Prueksadee, Jenjeera (Chulalongkorn Medical Journal, 2024)
A case report of Rosai-Dorfman disease (sinus histiocytosis with massive lymphadenopathy) of the breast is one of the rare diseases, characterized by benign proliferative disorder of histiocyte. Most of them occur within lymph nodes whereas the rest involve extranodal sites. Breast involvement is considered extremely rare but considerable because of radiological findings simulating breast cancer. We hereby report a case of a 59-year-old Thai woman who underwent screening mammography. Her biopsy resulted in abnormal histiocytes with S-100 protein expression, some of them with emperipolesis (lymphophagocytosis). Recognition of Rosai-Dorfman disease leads to correct diagnosis and further appropriate proper treatment strategy.